Evaluasi Program Sentra Kelautan Dan Perikanan Terpadu Di Koperasi Nelayan Kecamatan Bunguran Timur Kabupaten Natuna - Ibrahim Ibrahim; Jamhur Poti; Firman Firman (Concept: Journal of Social Humanities and Education, 2024)
Natuna Regency is one of the areas that has abundant marine potential and is one of the people's livelihoods. The backwardness of Natuna Regency as a lagging 3T region, foremost, and outermost is one of the obstacles that make Natuna Regency untouched from various assistance programs from the central government in providing assistance to the people in Natuna Regency. The Integrated Marine and Fisheries Center (SKPT) is one of the programs of the Ministry of Marine Affairs and Fisheries in the development of small islands and spatial-based borders and the marine and fisheries sector as the main driver. The main objective of this SKPT program is to utilize the marine and fisheries potential of Indonesia's outer islands to increase the capacity of the main actors in marine and fisheries and improve the welfare of the main actors in the marine and fisheries sector in a sustainable manner. The research method used descriptive qualitative with the number of informants 3 people. The results of this study are known that: (1) the effectiveness of the integrated marine and fisheries center program in the fishing cooperative of East Bunguran District, Natuna Regency is administratively effective, because the purpose of this program is clear, which is given to cooperatives and distributed to fishermen, (2) aid ships cannot be used because capital is needed and kapa cannot be used in the Natuna Sea, (3) that the adequacy of the integrated marine and fisheries center program in the fishing cooperative of East Bunguran District, Natuna Regency is not sufficient, (4) the assistance vessels provided have been distributed equally to the KUB in East Bunguran District, (5) the community responded positively and very enthusiastic with the assistance of the ship, (6) assistance was distributed appropriately, namely to fishermen in East Bunguran District. The conclusion of the evaluation of the integrated marine and fisheries center program in the East Bunguran District Fisherman Cooperative has not been successful because the assistance vessels provided cannot be used by fishermen with specifications that are not in accordance with the wishes of the community and the conditions of the Natuna Sea.